Sustainability in polymeric materials: A review on basic concepts, socioeconomic challenges, and innovations in the field of nanotechnology - Cardoso, Vitor de Freitas; Batista, Camila Nogueira da Silva; Moura, Mariana Loyola; Rocha, Lizandra Viana Maurat da; Gomes, Ana Catarina de Oliveira (Seven Editora, 2024)
This text was prepared collaboratively by the students of the undergraduate course in Nanotechnology at the Federal University of Rio de Janeiro (UFRJ), under the mediation and guidance of professors Lizandra Maurat and Ana Catarina Gomes, as part of the summative and formative evaluation processes of the discipline "Sustainability Applied to Polymeric Materials". The use of this active methodology intended to fix and summarize the topics covered in class, in addition to disseminating and discussing the theme, through an integrative review of fundamental concepts, socioeconomic challenges and advances related to the context. The growing need for research, study and basic knowledge of the physical chemistry of polymers was highlighted here, in order to conceive classifications and discussions in terms of sustainability, considering the complexity of the interactions between polymeric materials, society and the environment. This paper highlights the ecological and socioeconomic complications associated with these materials, as well as discusses emerging innovations in nanotechnology as potential solutions. It was possible, by integrating all the subjects, to link a comprehensive understanding of the topic, highlighting the importance of innovative approaches to overcome the challenges of the application and evaluation of polymeric materials, nanostructured or not. DOI:https://doi.org/10.56238/sevened2023.008-024